International flight‐related transmission of pandemic influenza A(H1N1)pdm09: an historical cohort study of the first identified cases in the United Kingdom. Issue 1 (7th November 2013) - Young, Nicholas; Pebody, Richard; Smith, Gillian; Olowokure, Babatunde; Shankar, Giri; Hoschler, Katja; Galiano, Monica; Green, Helen; Wallensten, Anders; Hogan, Angela; Oliver, Isabel
<x xml:space="preserve">Abstract</x> Background Transporting over two billion passengers per year, global airline travel has the potential to spread emerging infectious diseases, both via transportation of infectious cases and through in‐flight transmission. Current World Health Organization (WHO) guidance recommends contact tracing of passengers seated within two rows of a case of influenza during air travel. Objectives The objectives of this study were to describe flight‐related transmission of influenza A(H1N1)pdm09 during a commercial flight carrying the first cases reported in the United Kingdom and to test the specific hypothesis that passengers seated within two rows of an infectious case are at greater risk of infection. Methods An historical cohort study, supplemented by contact tracing, enhanced surveillance data and laboratory testing, was used to establish a case status for passengers on board the flight. Results Data were available for 239 of 278 (86·0%) of passengers on the flight, of whom six were considered infectious in‐flight and one immune. The attack rate (AR) was 10 of 232 (4·3%; 95% CI 1·7–6·9%). There was no evidence that the AR for those seated within two rows of an infectious case was different from those who were not (relative risk 0·9; 95% CI 0·2–3·1; P = 1·00). Laboratory testing using PCR and/or serology, available for 118 of 239 (49·4%) of the passengers, was largely consistent with clinically defined case status. Conclusions This study of A(H1N1)pdm09 does not support current WHO guidance regarding the contact tracing of passengers seated within two rows of an infectious case of influenza during air travel.